Estimating the Adoption Behaviour of Broccoli (Brassica oleracea var. italica) Cultivators with Respect to their Socio-economic Attributes in West Bengal - Sarkar, S.; Pradhan, K.; Biswas, S. (International Journal of Bio-resource and Stress Management, 2023)
The present study was conducted at Coochbehar-II block of West Bengal, India during 2011-12 and 2012-13 to estimate the adoption behaviour of the broccoli growers with respect to their biophysical, socioeconomic and socio psychological attributes. The study was conducted at Coochbehar-II block of West Bengal. The purposive as well as multistage random sampling procedures were followed to select the respondents of the study. The adoption behaviour was operationalized with the help of adoption index as a consequent variable. Fourteen antecedent variables were selected for the present study to explore the contribution in characterising the adoption behaviour of broccoli farmers. The data were collected with the help of structured interview schedule through personal interview method. The collected data were processed through descriptive statistics, correlation analysis, multiple regression analysis and factor analysis. The antecedent bio-physical variables like curd width, curd weight, yield, the socio-economic antecedent variables namely education, economic status, benefit cost ratio and horizontal expansion, the socio psychological antecedent variables like risk orientation and knowledge were found strongly associated with adoption behaviour of broccoli farmers. The predictor variables namely benefit cost ratio, effective farm size and economic status were strongly contributing in case of characterising the adoption behaviour of broccoli farmers. The study identified four distinct factors like biophysical and psychological orientation, socio-economic and educational exposure, socio-personal belongingness and family structure.